2002
DOI: 10.1038/sj.onc.1205003
|View full text |Cite
|
Sign up to set email alerts
|

A Myb dependent pathway maintains Friend murine erythroleukemia cells in an immature and proliferating state

Abstract: Friend murine erythroleukemia (MEL) cells are transformed erythroid precursors that are held in an immature and proliferating state but can be induced to dierentiate in vivo by treatment with a variety of chemical agents such as N, N-hexamethylene bisacetamide (HMBA). To investigate the role of Myb proteins in maintaining MEL cells in an immature and proliferating state we have produced stable transfectants in the C19 MEL cell line that contain a dominant interfering Myb allele (MEnT) under the control of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…entiation in C19 MEL cells and these cells provide a useful system to identify physiologically relevant c-Myb target promoters (Chen et al, 2002). Our experiments using this model have identified the CAIe promoter, which is downregulated during MEL cell differentiation, as a potential target of c-Myb activity.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…entiation in C19 MEL cells and these cells provide a useful system to identify physiologically relevant c-Myb target promoters (Chen et al, 2002). Our experiments using this model have identified the CAIe promoter, which is downregulated during MEL cell differentiation, as a potential target of c-Myb activity.…”
Section: Discussionmentioning
confidence: 93%
“…MEnT consists of the mouse c-Myb DBD fused to the transcription suppression domain of the Drosophila Engrailed protein (Badiani et al, 1994). Expression of MEnT in these stable transfectants is regulated by the ZnCl 2 -inducible mouse metallothionein I (MTH-I) promoter and induced expression of MEnT in C19 MEL cells provides a sufficient signal to induce differentiation (Chen et al, 2002). One of these transfectants, clone 17, was grown in culture for 4, 24 and 72 h with or without ZnCl 2 and total cellular RNA from each sample was analysed by differential display.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from a number of different laboratories have shown that the v-Myb protein is nuclear, binds to specific DNA sequences as a monomer, and can activate the expression of reporter genes (Boyle et al, 1984;Klempnauer et al, 1984;Biedenkapp et al, 1988;Garcia et al, 1991). In addition, both v-Myb and its normal cellular homologue c-Myb have been shown to be capable of activating gene expression in a variety of cell types Nishina et al, 1989;Weston and Bishop, 1989;Ibanez and Lipsick, 1990;Nakagoshi et al, 1992;Siu et al, 1992;Cogswell et al, 1993;Ku et al, 1993;Melotti and Calabretta, 1994;Burk et al, 1997;Worpenberg et al, 1997;Schlichter et al, 2001;Chen et al, 2002;Bartley et al, 2003;Rushton et al, 2003;Braas et al, 2004;Lang et al, 2005;Liu et al, 2006).…”
mentioning
confidence: 99%